Carbon quantum dots displaying dual-wavelength photoluminescence and electrochemiluminescence prepared by high-energy ball milling. (November 2015) - Wang, Lve; Chen, Xu; Lu, Yanluo; Liu, Changxia; Yang, Wensheng
Abstract: Carbon quantum dots (CQDs) with multiple surface states were prepared by high-energy ball milling a mixture of activated carbon and KOH, followed by ultrafiltration purification. The as-prepared CQDs exhibit dual-wavelength photoluminescence emission peaks. Most interestingly, the first emission peak is independent of excitation wavelength ( λ ex ) and the second one is dependent on λ ex and red shifts monotonically with increasing λ ex . Meanwhile, the as-prepared CQDs also present dual-wavelength electrochemiluminescence property.